Reconstruction of Bone Defects after Operations on Voluminous Maxillary Cysts - J. Pazdera; V. Zbořil; P. Tvrdý; Z. Kolář; M. Geierová; J. Novotný (Czech Dental Chamber, 2005)
The authors treated 125 patients with odontogenic jaw cysts of the volume larger than 2 cm3. In 75 of them the cystectomy was followed by reconstruction of the bone defect by lyophilized griaded allogenic spongious bone supplied by the Tissue Bank of the Faculty Hospital in Brno-Bohunice. The remaining 50 patients operated on in the usual way (cystectomy with primary suture of the wound) formed the control group. In the postoperative course the patients were subjected to control examination clinically and by radiography (CT examination was performed in selected patients with the use of modern imaging methods). In evaluating of the results the frequency of postoperative complications and the course of postoperative bone defects were compared.In 75 patients of the basic cohort 86% of them healed up without complications, partial elimination of bone grafts occurred in 8% and the grafts had to be removed in 5% for inflammatory complications, while postoperative relapse of the cyst was observed in 1%.In the control group of 50 patients treated in a classical clinical procedure, 76% of patients were healed up without any complications. A secondary healing of the wound occurred in 12% of patients, the healing was complicated by a putrid inflammation in 8% of patients and a postoperative relapse of the cysts was encountered in 4%.The use of allogenic bone grafts contributed to a remarkable acceleration of osteoinduction: the ossification of bone defects developed in relation to their volume as early as after 10-15 months after the operation. Application of the method for operations on cysts of edentulous jaws or those with few teeth made it possible to prevent deformation of the denture-bearing area bad and thereby to avoid the problems of subsequent prosthetic treatment.